2006
DOI: 10.1001/archinte.166.8.876
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms After Acute Myocardial Infarction

Abstract: Background: Depression is common in patients hospitalized with acute myocardial infarction (AMI). In the community, younger women are uniquely prone to depression. Whether younger women are also more likely to have depression during hospitalization with AMI is unknown.Results: Younger (Յ60 years) patients had higher mean PHQ scores than older patients (6.4 vs 5.0; PϽ.001) and women had higher mean PHQ scores than men (6.8 vs 5.2; PϽ.001). When stratified by both age and sex, younger women had the highest PHQ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(137 citation statements)
references
References 24 publications
9
119
1
4
Order By: Relevance
“…Validated standardized instruments were used to assess psychosocial and health status. These included (1) depression using the 9‐item Patient Health Questionnaire (PHQ‐9), with higher scores indicating increasing severity (range 0–27)19, 20, 21, 22; (2) perceived stress using the 14‐item Perceived Stress Scale (PSS), with higher scores indicating higher stress levels (range 0–40)23, 24; and (3) health status outcomes (patients’ physical limitations, angina frequency, and quality of life related to angina) using the Seattle Angina Questionnaire (SAQ; scores ranging from 0 to 100), with higher scores indicating better health status 25, 26, 27, 28, 29. In addition, detailed review of medical charts was conducted to better characterize the AMI phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Validated standardized instruments were used to assess psychosocial and health status. These included (1) depression using the 9‐item Patient Health Questionnaire (PHQ‐9), with higher scores indicating increasing severity (range 0–27)19, 20, 21, 22; (2) perceived stress using the 14‐item Perceived Stress Scale (PSS), with higher scores indicating higher stress levels (range 0–40)23, 24; and (3) health status outcomes (patients’ physical limitations, angina frequency, and quality of life related to angina) using the Seattle Angina Questionnaire (SAQ; scores ranging from 0 to 100), with higher scores indicating better health status 25, 26, 27, 28, 29. In addition, detailed review of medical charts was conducted to better characterize the AMI phenotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Both measures are feasible to use as screening instruments in clinical practice due to their brevity [13][14][15] . In patients with CAD and chronic heart failure (CHF), the PHQ-2 has been used in research on clinical depression, quality of life and heart rate variability 6,[15][16][17][18][19][20][21] , but its prognostic value is as yet to be determined in cardiac patients. By contrast, two studies have investigated the prognostic value of the PHQ-9.…”
Section: Introductionmentioning
confidence: 99%
“…In general, women are more likely to suffer depression than men, 3 and we found this to be true for patients with stable chronic angina. Various plausible biological and environmental mechanisms have been studied, including the role of sex hormones and women's social roles, to explain this sex disparity, but to date none have been conclusive.…”
Section: Discussionmentioning
confidence: 53%
“…After myocardial infarction (MI), the incidence of depression has been estimated to range between 10% and 40%, [1][2][3] and similar rates have been reported after coronary artery bypass graft (CABG). [4][5][6] Studies that have examined the impact of depression in patients who have experienced an MI have consistently found that it is associated with adverse outcomes.…”
Section: Epression Is Prevalent Among Patients With Coronarymentioning
confidence: 87%